2010
DOI: 10.1111/j.1600-0897.2010.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of APS after TTd Hyper-Immunization has a Different Outcome in BALB/c and C57BL/6 Mice

Abstract: We conclude that TTd immunization and i.v. application of monoclonal antibody 26 induced the same reproductive pathology and that the type of pathology is strain dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…In accordance with these results are our findings that TTd hyper-immunization does not lead to fetal resorption or thrombocytopenia in C57BL/6 mice. 20 The influence of applied TTd-hyper-immunization protocol on changes within aPL Abs pool was examined by three ELISA-based systems utilizing CL (alone or complexed with human b 2 GPI) or human b 2 GPI alone as antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these results are our findings that TTd hyper-immunization does not lead to fetal resorption or thrombocytopenia in C57BL/6 mice. 20 The influence of applied TTd-hyper-immunization protocol on changes within aPL Abs pool was examined by three ELISA-based systems utilizing CL (alone or complexed with human b 2 GPI) or human b 2 GPI alone as antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, vaccines such as tetanus toxoid and seasonal influenza, were found to be associated with the production of antiphospholipid antibodies in both human and animal models. 84,85 Induction of APS was possible in two non-prone mouse strain (BALBc and C57BL/6) mice that were hyperimmunized with tetanus toxoid boosted with aluminum hydroxide and complete Freud’s adjuvants (CFA) that are commonly used in other vaccines. 84,85 In these animal models, APS was associated with the development of prolonged coagulation time, thrombocytopenia and fetal loss.…”
Section: Asia Syndrome and Apsmentioning
confidence: 99%
“…Analyses of specific IgG subclass contributions to the entirety of the anti-ganglioside IgG pools showed that, for all experimental groups, a significant moiety of these contributing Abs belonged to subclasses IgG1 and IgG2c. 38 Anti-2 GPI antibodies in C57BL/6 and BALB/c mice Anti-b 2 GPI Abs can exert both beneficial (playing a homeostatic role) and deleterious effects, depending on their concentration, isotypic characteristics, affinity and fine epitope specificity. 46 We have already reported on the rise in the level of low-affinity anti-b 2 GPI Abs, and the Th2 prevalence dependent on Al-induced mechanisms, as well as decrease in fecundity in TTd hyperimmunized C57BL/6 mice.…”
Section: Idiotypic Network and Natural Antibodiesmentioning
confidence: 99%